Postoperative complications of percutaneous transluminal coronary angioplasty: a view to nursing care - Mejia , Judith Victoria Castillo (2021)
Objectives: To describe the main postoperative complications of percutaneous transluminal coronary angioplasty and to identify the respective nursing care. Methodology: bibliographic review and descriptive, exploratory study with a qualitative approach. Developed from consultations on official pages such as: Ministry of Health, Brazilian Association of Cardiology, National Agency for Health Surveillance (ANVISA) and Regional Health Council (COREN). The following databases were also consulted: CUIDEN, CINAHL, LILACS, SciELO and BDENF. Results: Although angioplasty is considered a safe procedure, there is the possibility of complications in the postoperative period. Peripheral vascular complications appear in the first 24 hours after the procedure and are theones that cause the greatest concern. Therefore, constant updating by the nurse is essential to identify these complications early, to guarantee safe care and reduce risks for the patient.